An Overview on Rumex dentatus L.: Its Functions as a Source of Nutrient and Health-Promoting Plant. (22nd July 2022) - Khalil, Atif Ali Khan; Zeb, Falak; Khan, Raees; Shah, Sayed Afzal; Küpeli Akkol, Esra; Khan, Ishaq N.; Khan, Jawad; Babar Jamal, Syed; Khuda, Fazli; Haider, Adnan; Ahmed, Saeed; Rehman, Naveed Ur
Abstract : Rumex dentatus L. (Polygonaceae), also known as toothed dock or Aegean dock, is a medicinal plant with a high culinary value in addition to being used as an ethnomedicinal plant. This review focuses on the botanical, nutritional, phytochemical, and pharmacological activities of R. dentatus, as well as the future prospects for systematic investigations into these areas. R. dentatus has been subjected to scientific evaluation, which has confirmed its traditional uses and demonstrated a wide range of biological and pharmacological potentials, including antioxidant, anticancer, antifungal, antibacterial, anti-inflammatory, and other biological properties. Phytochemical analyses showed the presence of anthraquinones, chromones, flavonoids, and essential oils. As a result of this current review, the medicinal significance of R. dentatus has been confirmed, and future research on its unexplored aspects, such as the identification of pharmacologically active chemical constituents and related mechanisms and safety, may be stimulated, with the goal of developing it into a drug.